Effects of Investment Climate on Entrepreneurial Growth in Abuja, Nigeria - Abomeh, Ofobruku, Sylvester; Peace, Nwakoby, Nkiru; Ileanaju, Omale, Musa; Janefrances, Okoye, Nwamake (International Journal of Economics, Business and Management Studies, 2019)
Currently, investment on SMEs in Abuja, Nigeria trailed behind that of many African cities. This study investigated the effect of investment climate on entrepreneurial growth in Abuja, Nigeria. The study focused specifically on the small and medium scale entrepreneurs within the six area councils in Abuja. The study adopted the survey method, involving the use of questionnaires as the major method for the generation of data. The data collected were analysed using regression as a statistical technique. The findings of the study revealed that government financial policy, such as interest rate significantly affects entrepreneurial growth in Abuja. Similarly, inadequate infrastructures were also observed to have significantly hindered entrepreneurial growth. The empirical findings led to the recommendation that for Nigeria’s investment climate to be favourable for entrepreneurs, financial policy and infrastructures development must be made conducive for local and foreign investors.